Bromelain as a Treatment for Osteoarthritis: a Review of Clinical Studies. Issue 3 (2004) - Brien, Sarah; Lewith, George; Walker, Ann; Hicks, Stephen M.; Middleton, Dick
Abstract : Bromelain, an extract from the pineapple plant, has been demonstrated to show anti-inflammatory and analgesic properties and may provide a safer alternative or adjunctive treatment for osteoarthritis. All previous trials, which have been uncontrolled or comparative studies, indicate its potential use for the treatment of osteoarthritis. This paper reviews the mechanism of its putative therapeutic actions, those clinical trials that have assessed its use in osteoarthritis to date, as well as considering the safety implications of this supplement for osteoarthritis and reviewing the evidence to date regarding the dosage for treating this condition. The data available at present indicate the need for trials to establish the efficacy and optimum dosage for bromelain and the need for adequate prospective adverse event monitoring in such chronic conditions as osteoarthritis.